2011
DOI: 10.1212/wnl.0b013e318230a17d
|View full text |Cite
|
Sign up to set email alerts
|

Age and disability accumulation in multiple sclerosis

Abstract: Development of SP is the dominant determinant of long-term prognosis, independent of disease duration and early relapse frequency. Age independently affects disability development primarily by changing probability and latency of SP onset, with little effect on the progressive course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
186
2
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(219 citation statements)
references
References 24 publications
20
186
2
6
Order By: Relevance
“…Other studies found no difference but, importantly, none concluded that disability accrual is faster in PPMS. 9,11,[22][23][24] Variability between these studies is likely methodologic and not intrinsic to Figure 2 Effect of immunomodulation on postprogression disability accumulation in BOPMS Survival curves from progressive MS onset to EDSS 6 are shown. Postprogression immunomodulatory medication use seemingly slows the pace of postprogression disability accumulation among patients with BOPMS who have ongoing relapses (A), but not clearly so among those who do not (B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies found no difference but, importantly, none concluded that disability accrual is faster in PPMS. 9,11,[22][23][24] Variability between these studies is likely methodologic and not intrinsic to Figure 2 Effect of immunomodulation on postprogression disability accumulation in BOPMS Survival curves from progressive MS onset to EDSS 6 are shown. Postprogression immunomodulatory medication use seemingly slows the pace of postprogression disability accumulation among patients with BOPMS who have ongoing relapses (A), but not clearly so among those who do not (B).…”
Section: Resultsmentioning
confidence: 99%
“…However, development of a progressive disease course and rate of postprogression disability accumulation seems to be age-dependent, and does not correlate with the rate of preprogression disability accumulation. 2,4,[7][8][9][10][11] Although age at progressive disease onset and pace of disability accumulation are similar across MS subtypes (e.g., PPMS vs SPMS), there is a wide range and distribution. This suggests that the presence or absence of other clinical parameters underlies the differences in long-term disability accrual between patients with progressive MS.…”
mentioning
confidence: 99%
“…The onset of progressive disease is age-dependent, and usually occurs at age 40-50 years; the frequency of relapses decreases with increasing age 77,78 . In a long-term analysis, age was identified (together with progressive MS and number of prior immune-modifying therapies) as an independent factor associated with neurological progression-free survival 60 .…”
Section: [H3] Age and Duration Of Diseasementioning
confidence: 99%
“…Its natural history has been extensively studied in Caucasian (CA) populations, and prognostic factors have been well recognized: being male, late age at the first symptom, high number of relapses in the onset of the disease, and short interval between initial relapses with poor recovery have been identified as predictive factors of long term disability 2,3,4,5,6,7,8,9,10,11 . While MS is a worldwide disease, its prevalence is higher in populations from western countries in the northern hemisphere compared to those from Africa, Asia and Latin America 12 .…”
Section: Disability and Progression In Afro-descendant Patients With mentioning
confidence: 99%